THE INFLUENCE OF DIET ON THE δ13C OF SHELL CARBON IN THE PULMONATE SNAIL HELIX ASPERSA - Stott L.D. (My University, 2002)
The influence of diet and atmospheric CO2 on the carbon isotope composition of shell aragonite and shell-bound organic carbon in the pulmonate snail Helix aspersa raised in the laboratory was investigated. Three separate groups of snails were raised on romaine lettuce (C3 plant, δ13C=-25.8%%), corn (C4 plant, δ13C=-10.5%%), and sour orange (12C-enriched C3 plant, δ13C=-39.1%%). The isotopic composition of body tissues closely tracked the isotopic composition of the snail diet as demonstrated previously. However, the isotopic composition of the acid insoluble organic matrix extracted from the aragonite shells does not track diet in all groups. In snails that were fed corn the isotopic composition of the organic matrix was more negative than the body by as much as 5%% whereas the matrix was approximately 1%% heavier than the body tissues in snails fed a diet of C3 plant material. These results indicate that isotopic composition of the organic matrix carbon cannot be used as an isotopic substrate for paleodietary reconstructions without first determining the source of the carbon and any associated fractionations. The isotopic composition of the shell aragonite is offset from the body tissues by 12.3%% in each of the culture groups. This offset was not influenced by the consumption of carbonate and is not attributable to the diffusion of atmospheric CO2 into the hemolymph. The carbon isotopic composition of shell aragonite is best explained in terms of equilibrium fractionations associated with exchange between metabolic CO2 and HCO3 in the hemolymph and the fractionation associated with carbonate precipitation. These results differ from previous studies, based primarily on samples collected in the field, that have suggested atmospheric carbon dioxide contributes significantly to the shell δ13C. The culture results indicate that the δ13C of aragonite is a good recorder of the isotopic composition of the snail body tissue, and therefore a better recorder of diet than is the insoluble shell organic carbon. Because the systematic fractionation of carbon isotopes within the snail is temperature dependent, the δ13C of the shell could provide an independent technique for estimating paleotemperature changes.
Keywords: PULMONATA; C-13/C-12; DIET; SHELLS; PALEOCLIMATOLOGY